2014
DOI: 10.3928/01484834-20131209-02
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Perceptions Regarding the Amount and Type of Written Feedback Required to Enhance Their Learning

Abstract: Effective feedback can enhance student learning, but limited evidence exists on whether nursing students actually use and learn from written feedback. This descriptive survey explored nursing students' perceptions regarding the amount and type of written feedback required to enhance their learning. In stage one, 362 students completed a 28-item questionnaire regarding feedback experiences and preferences; in stage two, 227 students selected a preferred feedback option for a final topic assignment. Findings rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
1
18
0
1
Order By: Relevance
“…Similarly, Ginsburg et al ., in a content analysis of written comments on IM residents’ ITERs, found that comments about a resident's ‘attitude or disposition’ were common, along with other commentary not linked directly to competencies . The problems associated with the writing of vague, dispositional comments that are subject to (mis)interpretation are not unique to medicine and can be found elsewhere in higher education …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ginsburg et al ., in a content analysis of written comments on IM residents’ ITERs, found that comments about a resident's ‘attitude or disposition’ were common, along with other commentary not linked directly to competencies . The problems associated with the writing of vague, dispositional comments that are subject to (mis)interpretation are not unique to medicine and can be found elsewhere in higher education …”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have proven the usefulness of WFB (Corcoran et al, 2014;Giles et al, 2014;Koh, 2010;and Rogers et al, 2012). Bailey and Vardi (1999), for instance, demonstrated the beneficial effects of feedback through their case study of a cycle of feedback in formative assessment.…”
Section: Utility Purpose and Focus Of Wfbmentioning
confidence: 99%
“…In universities, without adequate and effective feedback on their writing, students may not develop their academic writing skills and consequently they turn to plagiarism and other malpractices. In such a scenario, the role of written feedback assumes critical importance, because it helps students learn about their strengths and weaknesses (Corcoran, Halverson, & Schindler, 2014;Giles, Gilbert, & McNeill, 2014;and Orrell, 2006) and build their competence in academic writing.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In addition, researchers believe that WFB can help the students to improve their academic writing skills [3,[6][7][8][9] and making them reflect on their progress. [1,2,10] Furthermore, it is also used to justify the students' grade or rank, [11] and offers an opportunity for experiential learning. [12,13] However, the provision of WFB is affected by a number of personal and organizational factors.…”
Section: Introductionmentioning
confidence: 99%
“…(2) What are the practices of teachers regarding written feedback to students? (3) What factors influence teachers' practices of providing quality written feedback to their students?…”
Section: Introductionmentioning
confidence: 99%